Resolution of disputes in administration of estates in Malaysia : proposing mediation as an effective means - Muhammad Amrullah bin Drs Nasrul (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2018)
The purpose of this research is to examine the issue of family dispute among the beneficiaries in the administration of estate. It analyses the nature of family dispute as to see how the occurrence of family dispute affects the administration of estate, resulting in a delay in the management and distribution of the deceased's estate. This research also analyses the practicality of mediation as a mode of dispute resolution in addressing family disputes among the beneficiaries. In relation to this, the research adopts a non-doctrinal approach in determining the effectiveness of the practice by the administrative bodies in dealing with family dispute cases. Data in the form of primary and secondary sources are collected through a set of methods by way of interviews, case file references and library-based study. The research found that three factors lead to the occurrence of a family dispute, ranging from lack of knowledge of the beneficiaries, personal attitudes of the beneficiaries, as well as communication between the beneficiaries. Apart from this, the research also shows that there is no uniformity of practice by the three administrative bodies namely the civil High Court, the Estate Distribution Unit and Amanah Raya Berhad (ARB) in addressing family dispute suffered by the beneficiaries. Despite various practice, it was found that issues on family dispute do not receive a sufficient attention from the administrative bodies due to lack of effective means in addressing such issue. On the other hand, analysis on mediation shows that mediation excels in resolving the family dispute in estate administration which is mainly due to its effectiveness in addressing the emotional aspects of the parties. Therefore this research proposes that mediation is applied into the practice of the administrative bodies in addressing family dispute in the administration of estate.